Euro Conditionality Hinges on Positive Convergence - Michala Marcussen (Intereconomics)
Abstract The present cocktail of a bleak economic outlook combined with high inflation and rising interest rates has raised questions as to whether a new euro debt crisis might emerge. Euro area sovereign spreads have widened, but not to “unwarranted” levels, unlike the situation that prevailed during the European debt crisis. A replay of the funding fears, which drove the euro area debt crisis a decade ago, seems unlikely today with the extensive toolkit now in place.